2010
DOI: 10.1111/j.1574-6941.2010.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous members of cluster III Defluviicoccus have the in situ phenotype expected of a glycogen-accumulating organism in activated sludge

Abstract: The in situ ecophysiology of alphaproteobacterial filamentous Cluster III Defluviicoccus present in enhanced biological phosphorus removal (EBPR)-activated sludge systems was evaluated using FISH-MAR and histochemical staining methods. These organisms, sharing the Nostocoida limicola morphotype, are known to be responsible for serious episodes of activated sludge bulking. The data presented here also demonstrate an ability to assimilate short-chain fatty acids and synthesize poly-β-hydroxyalkanoates (PHA) anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…GAO phenotype has also been demonstrated for the sole isolate, D. vanus , a member of cluster 1 (Maszenan et al, 2005; Wong and Liu, 2007). Anaerobic carbon storage as PHA has also been shown in situ for clusters 3 and 4 (McIlroy et al, 2010). In this study, OTUs representing clusters 2 and 3 made up the majority (>90%) of amplicon reads assigned to the genus, which is consistent with FISH analyses of full-scale systems ( Figure 8 ; Burow et al, 2007; McIlroy and Seviour, 2009).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…GAO phenotype has also been demonstrated for the sole isolate, D. vanus , a member of cluster 1 (Maszenan et al, 2005; Wong and Liu, 2007). Anaerobic carbon storage as PHA has also been shown in situ for clusters 3 and 4 (McIlroy et al, 2010). In this study, OTUs representing clusters 2 and 3 made up the majority (>90%) of amplicon reads assigned to the genus, which is consistent with FISH analyses of full-scale systems ( Figure 8 ; Burow et al, 2007; McIlroy and Seviour, 2009).…”
Section: Resultsmentioning
confidence: 84%
“…The application of molecular methods has also allowed the study of the putative GAO in situ where the phenotype has been at least partially confirmed for: the actinobacterial genus Micropruina and closely related sbr-gs28 taxon (Kong et al, 2001), the gammaproteobacterial family Competibacteraceae (Kong et al, 2006) and CCM19a phylotype (probe Gam445) (Kong et al, 2007), the alphaproteobacterial genus Defluviicoccus (Wong et al, 2004; Meyer et al, 2006; Burow et al, 2007; Wong and Liu, 2007; McIlroy et al, 2010), and the betaproteobacterial genera Propionivibrio (Albertsen et al, 2016), and Spb280 (probe Bet65; Kong et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Two types of GAO are often observed in full and laboratory-scale EBPR systems: 'Candidatus Competibacter phosphatis' of the class Gammaproteobacteria (Crocetti et al, 2002;Kong et al, 2002) and Defluviicoccus-related GAO of the Rhodospirillaceae family in the class Alphaproteobacteria (Wong et al, 2004;Wong and Liu, 2006;McIlroy and Seviour, 2009;Mielczarek et al, 2013). For the Defluviicoccus-related GAO, tetrad-forming (DTFO) (cluster I, II and IV) and filamentous clades (cluster III) have been characterized EBPR systems as potential PAO competitors (Wong et al, 2004;Burow et al, 2007;Wong and Liu, 2007;McIlroy and Seviour, 2009;McIlroy et al, 2010). These clusters have varying predominance in full and laboratoryscale EBPR systems; for example, cluster I and III prevalence is associated with laboratory and full-scale systems respectively, while cluster II have been observed to predominate in both systems (Wong et al, 2004;Burow et al, 2007;Nittami et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When culture-independent techniques were implemented, it was found that large coccobacillus-shaped Candidatus Competibacter phosphatis [9,10] in the Gammaproteobacteria (hereafter referred to as Competibacter or GB-GAO), and Defluviicoccus-related species (Dv-GAO) in the Alphaproteobacteria [11,12], are the most frequently reported GAOs in both lab-scale and full-scale deteriorated EBPR reactors. There is a distinct differentiation within the GAOs; GB-GAOs are composed of at least seven sub-groups [9], while DvGAOs comprise four clusters [13,14].…”
Section: Introductionmentioning
confidence: 99%